(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Residential construction projects arethe major part of overall construction industry. Cost, schedule overruns and rework are common in this industry and therefore various construction management practices can be applied in residential construction projects. Hence this area has been focused for the study. This study concerned about how just in time technique can be applied at the residential construction projects in Pune city.Hence the purpose of this paper was to investigate the applicability of JIT and current situations on the construction site through questionnaire survey, site observations and interviews. This survey helped to understand and identify barriers and difficulties that may be encountered in the implementation of just in time technique and propose effective and efficient means of technique to be adopted by the construction projects in Pune city.